An introduction to language - Fromkin, Victoria; Hyams, Nina; Rodman, Robert (Singapore Cengage, 2017)
This book offers an entirely up-to-date look at language studies and linguistics in today's world. The authors examine grammatical subjects (e.g., morphology, syntax, semantics, phonetics, phonology), childhood language development and adult secondary language acquisition, and the tremendous leap in knowledge achieved in neurolinguistics.
Keywords: Cơ bản